Madarisut Tafsir Fi Qarnis Sahabah (BIDAYAH: STUDI ILMU-ILMU KEISLAMAN, 2017)
Sahabat holds a very important role in understanding the Qur'an, but not all the companions proficient in understanding the Qur'an (Tafseer science), it is because not all friends have a chance together the Prophet and other factors as well, the ability of the differents. One of them is the ability to understand the language of the Qur'an, sometimes the Qur'an uses diverse vocabulary in describing an event. In solving this problem, some friends there who took time to constantly work with the Prophet in hearing assessment study, which the Prophet Convey. Until such a situation inherited by pal Teach Tafsir In the generation shaped Tabi'in small halaqah. This paper describes the overall on how the development of Tafsir it through schools of interpretation that are in every city that has been conquered by the Islamic Army in the days of Sahabah and Tabi'in